1999
DOI: 10.1161/01.cir.100.24.2455
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Delayed Rectifier K + Currents in Dogs With Chronic Complete Atrioventricular Block and Acquired Torsades de Pointes

Abstract: Background-Acquired QT prolongation enhances the susceptibility to torsades de pointes (TdP). Clinical and experimental studies indicate ventricular action potential prolongation, increased regional dispersion of repolarization, and early afterdepolarizations as underlying factors. We examined whether K ϩ -current alterations contribute to these proarrhythmic responses in an animal model of TdP: the dog with chronic complete atrioventricular block (AVB) and biventricular hypertrophy. Methods and Results-The wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
169
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(185 citation statements)
references
References 37 publications
11
169
2
Order By: Relevance
“…This I Ks reduction was considered the cause of APD prolongation in the LV. 5 In the present study, we found a 52% to 120% prolongation of the QT interval and a 20% to 60% increase in APD in the LV myocytes from the rabbit model. The 50% decrease of I Kr in addition to the 55% decrease of I Ks observed in our study may explain the more pronounced prolongation of the AP compared with that in the dog model.…”
Section: Downregulation Of I Kr and I Ks In Chronic Avbsupporting
confidence: 56%
See 3 more Smart Citations
“…This I Ks reduction was considered the cause of APD prolongation in the LV. 5 In the present study, we found a 52% to 120% prolongation of the QT interval and a 20% to 60% increase in APD in the LV myocytes from the rabbit model. The 50% decrease of I Kr in addition to the 55% decrease of I Ks observed in our study may explain the more pronounced prolongation of the AP compared with that in the dog model.…”
Section: Downregulation Of I Kr and I Ks In Chronic Avbsupporting
confidence: 56%
“…5 The increase of APD in AVB myocytes was 10% to 30% in the LV (depending on the cycle length) under baseline conditions. 4 There was a 50% reduction of I Ks and no change of I Kr in the LV.…”
Section: Downregulation Of I Kr and I Ks In Chronic Avbmentioning
confidence: 91%
See 2 more Smart Citations
“…Mechanistically, it has been reported that during bradyarrhythmias, downregulation of the repolarizing currents -rapid and slow delayed rectifier K + currents (I Kr and I Ks , respectively) -results in QT interval prolongation and TdP (15)(16)(17)(18). These findings were based on canine and rabbit models of chronic complete AV block that showed reduction in I Kr and I Ks , and altered L-type Ca 2+ current, with other currents (inward Na + current, transient outward K + current and inward rectifier K + current) remaining normal (15,16,18).…”
Section: Mechanism Of Tdp In Complete Av Blockmentioning
confidence: 99%